Strengthening Business Management Literacy Through Community Service Programs in China - Qi Lou (CV Edujavare Publishing, 2025)
Business management literacy has become increasingly important in supporting entrepreneurial sustainability, organizational adaptability, and community economic resilience in contemporary economic environments. Rapid technological transformation, digital business expansion, and global market competition require local business communities to possess strong managerial competence and strategic business understanding. This community service program aimed to strengthen business management literacy among community business participants in China through participatory educational activities and collaborative mentoring approaches. The program employed a qualitative participatory method involving small business owners, local entrepreneurs, family business operators, and community business groups through workshops, business simulations, mentoring sessions, and collaborative discussions. Educational activities focused on financial management, business planning, leadership development, operational coordination, digital business adaptation, and customer communication strategies. The results demonstrated significant improvement in participants’ managerial competence, financial literacy, organizational awareness, communication skills, and understanding regarding digital business systems. Participants also showed increased confidence in applying structured business planning, budgeting practices, and technology-based marketing strategies within their business operations. In addition, collaborative learning activities positively influenced participants’ problem-solving abilities, entrepreneurial motivation, and organizational adaptability. Despite challenges related to differences in educational backgrounds, technological familiarity, and managerial experience, participatory educational approaches and continuous mentoring contributed positively to strengthening sustainable business management practices. Overall, the implementation of community-based business management education provided valuable opportunities for improving entrepreneurial resilience, strengthening organizational sustainability, and supporting long-term economic participation within local business communities in China.